The Impact of Ai Techinology Guided Weapons in the War on Gaza. - Claire Arech Nyibol (Uganda Christian University, 2025)
This study explores the impact of Artificial Intelligence (AI) technology-guided weapons on the observance of International Humanitarian Law (IHL) principles during the war in Gaza, with a focus on the 2023 Operation Swords of Iron. Through a detailed literature review and qualitative analysis of secondary data—including legal documents, scholarly articles, military reports, and satellite imagery—the research assesses how AI-guided weapons influence the principles of distinction, proportionality, necessity, and humanity in armed conflict. While proponents argue that AI enhances precision and minimizes collateral damage, findings reveal a significant gap between theoretical capabilities and real-world outcomes, particularly in densely populated areas like Gaza. The study identifies elevated civilian casualty rates and widespread infrastructure destruction, suggesting failures in upholding IHL principles despite the use of advanced AI targeting systems. These discrepancies highlight unresolved issues around accountability, legal oversight, and ethical deployment of AI in warfare. The research concludes with urgent calls for robust international regulation, enhanced human oversight, and mechanisms for post-conflict accountability to ensure that the use of AI in warfare aligns with humanitarian and legal standards.
under graduate